Procedimientos teatrales de sacralización en el auto sacramental El divino Orfeo de Pedro Calderón de la Barca - Friedrich, Sabine (Peter Lang AG, 2019)
The article proposes to analyze the sacralization of Orpheus as a sacred object in its ambivalence between Catholic appropriation and the manifestation of the instability and contingency of this process. Calderon's auto sacramental repeats the Christian appropriation of the myth of Orpheus a lo divino in an exemplary, determined and unambivalent manner. But at the same time the theatrical performance of the auto exposes the processes of sacralizations in all its arbitrariness.
CRIS-Team Scopus Importer:2024-12-16